Psoriasiform lesions as a side effect of SGLT-2 therapy - Gałązka, Jakub Krzysztof; Domagalski, Łukasz; Homa, Piotr; Hoffman, Zofia (Quality in Sport, 2023)
SGLT-2 inhibitors (flozins) are one of the new classes of anti-diabetic drugs, used from 2012. They are highly recommended in case of intolerance or contraindication of metformin, but in Poland they are used usually as third-line drug after metformin and sulfonylurea. They growing popularity is caused by their significance in cardiovascular risk reduction and preventive role in according to diabetes complications like chronic kidney disease, or diabetes-induced dementia. The aid of this article is to summarize the knowledge on the risk of psoriasis development in diabetic patients cured with flozins. In according to the newest studies, flozins may be considered as a pro-psoriatic factor, increasing the risk of this skin disease, especially in patients with diabetic kidney disease. But on the other hand, SGLT-2 inhibitors have significantly decreasing effect on cardiovascular risk, which is increased in psoriatic patients.